2018
DOI: 10.1371/journal.pone.0192597
|View full text |Cite
|
Sign up to set email alerts
|

A new prediction model for operative time of flexible ureteroscopy with lithotripsy for the treatment of renal stones

Abstract: This study aimed to develop a prediction model for the operative time of flexible ureteroscopy (fURS) for renal stones. We retrospectively evaluated patients with renal stones who had been treated successfully and had stone-free status determined by non-contrast computed tomography (NCCT) 3 months after fURS and holmium laser lithotripsy between December 2009 and September 2014 at a single institute. Correlations between possible factors and the operative time were analyzed using Spearman’s correlation coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
1
21
0
2
Order By: Relevance
“…In their study including 154 patients, Taş et al (26) investigated the incidence of ureteral stenosis in patients undergoing pneumatic lithotripsy for the treatment of distal ureteral stones and found high rates of ureteral J stent implantation associated with increased mucosal edema, ureteral perforation, and high stone burden. In a recently published study, it was also reported that in patients who underwent flexible URS, the high values of stone HU prolonged the operative time and were associated with residual stone fragments (27). As the HU value indicating stone fragility increases, fragmentation of the stone may become more difficult, increasing the possibility of residual stones and requirement of ureteral J stent placement.…”
Section: Discussionmentioning
confidence: 97%
“…In their study including 154 patients, Taş et al (26) investigated the incidence of ureteral stenosis in patients undergoing pneumatic lithotripsy for the treatment of distal ureteral stones and found high rates of ureteral J stent implantation associated with increased mucosal edema, ureteral perforation, and high stone burden. In a recently published study, it was also reported that in patients who underwent flexible URS, the high values of stone HU prolonged the operative time and were associated with residual stone fragments (27). As the HU value indicating stone fragility increases, fragmentation of the stone may become more difficult, increasing the possibility of residual stones and requirement of ureteral J stent placement.…”
Section: Discussionmentioning
confidence: 97%
“…First of all, because data in this study were obtained from benchtop model experiments, it was impossible to reproduce all physiological factors that occurred when performing lithotripsy in living patients and the results can be affected by surgeons' experience. [12] The findings of this study should be proven through a well-designed clinical trial. Second, this study was limited to artificial stone mimicking a single stone type.…”
Section: Plos Onementioning
confidence: 81%
“…Among these variables, the stone number has a particularly large effect [ 32 ], and patients with a solitary calyceal calculus have a longer RIRS operation time and decreased SFR compared to patients with multiple calyceal calculi [ 33 , 34 ]. Additionally, the HU of the stone has an effect on the fragmentation efficiency and operation time in RIRS, and as HU increases [ 35 ], the operation time [ 36 ] as well as the total laser energy and total laser time increases, which thereby decreases the fragmentation efficiency and the SFR [ 37 ]. If there are a large number of renal stones or if the HU value is high, the operation time increases, and the fragmentation efficiency decreases while performing RIRS because of the increased washing pressure that leads to increased movement of broken stones, possibly resulting in bleeding in the renal mucosa, which leads to an obstruction of the visual field, causing fatigue for the urologist.…”
Section: Discussionmentioning
confidence: 99%